TENG estimation model of voltage production for buoys using particle swarm optimization. (August 2022) - Cestaro, Henrique; Mathias, Nuno; Gonçalves, Nelson D.; Morais, Tiago
Abstract: Oceanic surface buoys are known to have energetic demands for long-term stays at sea. Currently, batteries and solar panels have been use to cope with this need. Nonetheless, they are prone to damage and need replacement. Moreover, solar panels only function with sunlight, thus reducing their reach to some regions. Triboelectric nano-generators (TENG) are energy harvesting devices, capable of converting mechanical energy into electricity, by triboelectric effect and electrostatic induction. Their high efficiency, low manufacturing price and high power density make it ideal for wave energy conversion. In this paper, based on laboratory results obtained for a TENG model on a navigational buoy, a voltage production estimation model was generated using Particle Swarm Optimization (PSO), which can be fed with Boundary Element Method (BEM) simulations as input. The conclusion stated that PSO is a reliable methodology allowing for a quick estimation of voltage output for a given geographical region. It also becomes clear that coupling with existing BEM software is capable. Highlights: Modelling of voltage production of triboelectric nano-generators on buoy. Particle Swarm Optimization applied to define best voltage modelling parameters. Development of a numerical model relating the buoy motion and the voltage production.